Facial Nerve Paresis in Ramsay Hunt Syndrome - iltania mince (Faculty of Medicine, Universitas Andalas, 2024)
Introduction: Ramsay Hunt syndrome (SRH) is known as otic herpes zoster or geniculate ganglion herpes zoster, which is a late complication of Varicella-Zoster Virus (VZV) infection, which causes inflammation of the geniculate ganglion of cranial nerve VII. The SRH triad is ipsilateral facial paralysis, otalgia, and vesicular rash. Case Report:28 year old man with complaints of slanted face since 5 days ago. Right ear pain occurred 2 weeks ago, 1 day later a fluid-filled nodule appeared on the right earlobe and right cheek. On physical examination, yellowish crusts were found on the right side of the face, the auris dextra showed erythema and crusting in the turbinate and antihelix regions. In the Schirmer test the ratio of right and left tears is > 50%, the acoustic reflex is right (-) left (+). The patient was diagnosed with House-Brackmann grade III peripheral facial nerve paresis, good motor function 70% at the level of the geniculate ganglion et causaRamsay Hunt syndrome. Patients are given antiviral therapy, high doses of corticosteroids tapering offand physiotherapy. Conclusion: Management of patients with Ramsay Hunt syndrome by administering antivirals, high doses of corticosteroids, physiotherapy and rehabilitation.Keywords: ramsay hunt syndrome, varicella zoster virus, herpes zoster oticus